A Countable System of Fractional Inclusions with Periodic, Almost, and Antiperiodic Boundary Conditions. (14th June 2021) - Salem, Ahmed; Al-Dosari, Aeshah
Abstract : This article is dedicated to the existence results of solutions for boundary value problems of inclusion type. We suggest the infinite countable system to fractional differential inclusions written by D α ABC ν i t ∈ Y i t, ν i t i = 1 ∞ . The mappings y i t, ν i t i = 1 ∞ are proposed to be Lipschitz multivalued mappings. The results are explored according to boundary condition σ ν i 0 = γ ν i ρ, σ, γ ∈ ℝ . This type of condition is the generalization of periodic, almost, and antiperiodic types.